2015
DOI: 10.1039/c5ra16581d
|View full text |Cite
|
Sign up to set email alerts
|

A copper(ii)–thioamide combination as a robust heterogeneous catalytic system for green synthesis of 1,4-disubstituted-1,2,3-triazoles under click conditions

Abstract: One-pot synthesis of 1,4-disubstituted-1,2,3-triazoles 3 using copper(ii)–thioamide combination was reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 34 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…On the other hand, Cu(II) species without deliberate addition of a reducing agent for CuAAC reactions have also been investigated. The mechanistic studies indicated that the real catalytic Cu(I) species were generated in a short induction period via reducing Cu(II) salts by alcoholic solvents [127], sodium azide [46,128], or thiobenzanilide [129] especially in the three-component 1,3-dipolar cycloaddition for 1,4-disubstituted 1,2,3-triazoles synthesis. For instance, the recently reported 2-pyrrolecarbaldiminato-Cu(II) complexes efficiently catalyzed three-component 1,3-dipolar cycloaddition reaction of benzyl halides and sodium azide with terminal alkynes in water at r.t., leading to the synthesis of several regioselective 1,4-disubstituted 1,2,3-triazoles in 55-97% yield [130].…”
Section: Cuaacmentioning
confidence: 99%
“…On the other hand, Cu(II) species without deliberate addition of a reducing agent for CuAAC reactions have also been investigated. The mechanistic studies indicated that the real catalytic Cu(I) species were generated in a short induction period via reducing Cu(II) salts by alcoholic solvents [127], sodium azide [46,128], or thiobenzanilide [129] especially in the three-component 1,3-dipolar cycloaddition for 1,4-disubstituted 1,2,3-triazoles synthesis. For instance, the recently reported 2-pyrrolecarbaldiminato-Cu(II) complexes efficiently catalyzed three-component 1,3-dipolar cycloaddition reaction of benzyl halides and sodium azide with terminal alkynes in water at r.t., leading to the synthesis of several regioselective 1,4-disubstituted 1,2,3-triazoles in 55-97% yield [130].…”
Section: Cuaacmentioning
confidence: 99%
“…[24][25][26][27] Triazoles are an important class of heterocyclic compounds exhibiting a wide range of biological and medicinal properties. In continuation of our interest in the synthesis of various triazole derivatives, [28][29][30][31][32][33][34][35] in this study, new mesoporous silicacoated magnetic nanoparticles (Fe 3 O 4 @SiO 2 @IDA) have been prepared and applied for the synthesis of various 1,4-disubstituted-1,2,3-triazole derivatives. The hybrid nanocatalyst was synthesized by the sol-gel method from Fe 3 O 4 , tetraethoxysilane (TEOS) and 3-chloropropyl triethoxysilane (CPTES), and iminodiacetic acid (IDA) as precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Common drugs such as glibenclamide [13], sultiame [14], and COX-II inhibitors Piroxicam [15], Ampiroxicam [16], and Celecoxib [17] containing a sulfonyl moiety, which displays potential activity across a variety of biological targets. The sulfonamides are organic sulfur compounds which have attracted the attention for their better pharmacological activity [18][19][20]. It is interesting to note that the sulfonamide containing moiety is known to have some biological and pharmaceutical properties, such as, antitumor, antibacterial, thrombin inhibition, and antifungal activities [21][22][23].…”
Section: Introductionmentioning
confidence: 99%